Comparative seasonality and diets of German (Vespula germanica) and common (V. vulgaris) wasp colonies in Manawatu, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Zoology at Massey University - Godfrey, Peter Lance (Massey University, 1995)
German wasp (Vespula germanica) and common wasp (v. vulgaris) colonies were studied in urban and rural habitats in Manawatu, from January to August 1993. Relative abundance of colonies, nest site preferences, colony dynamics, phenology and diet are described. Data quantifying vespulid wasp nest abundance in Manawatu between 1991-1994 were sourced from pest control companies and the Manawatu-Wanganui Regional Council. These data were compared with rainfall records for the same period. Over 75% of nests examined in urban and rural Manawatu were built by common wasps. This trend persisted through the season with German wasps accounting for no more than 28% of nests reported in any one month. Most reports of wasps were made in January, with February and March also being high. Heavy rainfall in spring appeared to promote colony formation in the following year. Continued high rainfall between January-June, especially over 600 mm appeared, however, to suppress colonies during this time. Nest drowning is a possible reason for this. Different nest site preferences between the two species were evident in urban and rural habitats. Over half of all urban common wasp nests and a third of urban German wasp nests reported were in sites associated with buildings. Nests in such sites grow faster and larger than those in other sites. In contrast, all rural German wasp nests and 85% of rural common wasp nests were built in the ground. The invasion of Manawatu by common wasps does not appear to have modified the nest site preferences of German wasps. Seasonal traffic rates for both species were similar, with colonies peaking in late March. Common wasp traffic rates were significantly higher in January-February, probably because of earlier nest initiations. Prior to queen production common wasp colonies were most active in the early afternoon. Around the time of queen production early evening activity increased, possibly as a result of the seasonal decrease in day length. Nests with high numbers of worker/male cells built before male production began produced significantly more queens than those with fewer cells. Although similar in size to German wasp nests, common wasp nests contained more queen cells. Cell weights differed between the castes and species. German wasp nests therefore required more than twice as much effort to build as a common wasp nest of a similar size. The possible competitive effects of such differences are discussed. Manawatu German wasp colonies appear to produce males earlier (early February) than common wasp colonies (early March). The reverse applies to queen production which may have started earlier (March 12) in common wasp colonies than in German wasp colonies (March 20). However, variation within and between the species does occur. The egg laying ability of the founder queen appears to limit oviposition in worker/male cells but the availability of empty queen cells appears to limit oviposition in queen cells. The size of the worker force limits the number of larvae that can be cared for. Reproductives were seen leaving nests from early May and continued until the colonies died. In an overwintering German wasp nest production of all three castes were at levels equivalent to an annual nest at peak. German wasp foragers returned with a higher percentage of protein items (16%) than common wasp foragers (11%). Similar percentages of woodpulp were returned to colonies by both species. Diptera, Lepidoptera. Araneae, and Hemiptera were the main animal prey returned to urban and rural colonies. German wasp foragers returned with prey items that were significantly heavier than those carried by common wasps but woodpulp weight did not differ. However, common wasp colonies killed more invertebrates to meet their needs, suggesting that they represent a substantial threat to invertebrate communities. Both prey provision and woodpulp foraging increased dramatically with the onset of queen rearing, indicating the increased needs of colonies at this time. The ecological significance of woodpulp foraging on both species is discussed. Key areas for future wasp research that are applicable within Manawatu and more widely in New Zealand, are outlined. Main areas needing investigation concern aspects of colony dynamics and phenology.
Keywords: Vespa germanica; Vespula vulgaris; New Zealand; Palmerston North; Manawatu District